The Evolution of Corporate Accounts of Scandals From Exposure to Investigation - Gottschalk, Petter (The British journal of criminology, 2020)
We extend research on how corporations respond to scandals by examining the evolution of the accounts that are developed by corporate agents after a scandal becomes public. Guided by the theory of accounts and a recently developed perspective on crisis management, we examine how the accounts developed by 12 corporations caught up in highly publicized scandals changed from the time of initial exposure to the issuance of an investigative report. Our analysis shows that denial of wrongdoing in several cases is replaced by admission of wrongdoing and scapegoating, while obfuscation of wrongdoing is replaced by denial or acceptance of responsibility and scapegoating. We conclude with a discussion of the broader managerial and social implications of our analysis and how it furthers our understanding of the ability of corporations to weather serious scandals.